2015
DOI: 10.1039/c5cp02252e
|View full text |Cite
|
Sign up to set email alerts
|

Novel compounds in the Zr–O system, their crystal structures and mechanical properties

Abstract: With the motivation of exploring new high-strength ceramics, ab initio evolutionary simulations are performed to search for all the stable compounds in the Zr-O system. We have found that not only the traditional compound ZrO2, but also the ordered suboxides R3̅-Zr6O, R3̅c-Zr3O, P3̅1m-Zr2O and P6̅2m-ZrO are stable at zero pressure. The crystal structure of semimetallic P6̅2m-ZrO consists of Zr-graphene layers and can be described as an intercalated version of the ω-Zr structure. An interesting massive Dirac co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 52 publications
(57 reference statements)
0
17
0
Order By: Relevance
“…P 62m-ZrO and P 62m-HfO are formed on x-Zr and x-Hf, and exhibit interesting structures and electronic properties. 9,20 Besides, P 62m-TiO has been proven to be the ground state of titanium monoxide and it has been experimentally detected using XRD in Amano's work. 11 There is a phase transition for ZrO at 72 GPa, from the hexagonal P 62m-ZrO with fivefold coordination of oxygen atoms to an orthorhombic Pmma-ZrO structure with sixfold coordination of oxygens ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…P 62m-ZrO and P 62m-HfO are formed on x-Zr and x-Hf, and exhibit interesting structures and electronic properties. 9,20 Besides, P 62m-TiO has been proven to be the ground state of titanium monoxide and it has been experimentally detected using XRD in Amano's work. 11 There is a phase transition for ZrO at 72 GPa, from the hexagonal P 62m-ZrO with fivefold coordination of oxygen atoms to an orthorhombic Pmma-ZrO structure with sixfold coordination of oxygens ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5 In addition, Furuta and Motohashi 6 found a cubic ZrO (a ¼ 4.62 Å ) on a zircaloy oxidized in steam at 1000 C. Ni 7 observed thin intermediate oxide layers with composition close to ZrO. Theoretical calculations [8][9][10] indicated that hexagonal P 62m-ZrO instead of NaCl-type ZrO is the ground state of zirconium monoxide, and P 62m-ZrO should be stable up to 1000 K. 8,9 Even though P 62m-ZrO had not been experimentally reported, just recently, the experiment 11 successfully synthesized the P 62m-TiO by using a bismuth flux and demonstrated that NaCl-type TiO was actually a hightemperature phase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is useful in practice to show the directional variation of Young's modulus by three-dimensional diagrams, where deviations from sphericity directly reflect the degree and direction of anisotropy. We calculated the elastic anisotropy of five special phases: P62m- calculations [29], therefore the band structure of P62m-HfO calculated by HSE06 is supposed to be similar. However the more accurate approach HSE06 result turns out that P62m-HfO has the tiny band gap 0.112 eV between the conduction band and valence band while DFT-GGA band structure shows that very few states at the Fermi level and P62m-HfO should be a semimetal.…”
Section: Mechanical Properties Of Hf-o Compoundsmentioning
confidence: 99%
“…In paper [24], the following thermo-dynamically stable compounds were revealed: Zr 6 O, Zr 3 O, Zr 2 O, ZrO and ZrO 2 , as well as the Gibbs powers, at which the formation of the above compounds takes place, were established ( Depending on the temperature-temporal and gas-dynamics parameters of zirconium interaction with oxygen-containing medium, in the near-surface layer of metal, an oxide film and/or only a diffusion layer is formed. Paper [10] also shows that in the "Zr-O" system there is only one stable oxide ZrO 2 , which has several modifications.…”
Section: а B C Dmentioning
confidence: 99%